Kanal easy German sebagai media pembelajaran Bahasa Jerman berbasis kehidupan - Dameria, Cut Nyak; Rahmadani, Fidyah Wahyu; Bela, Nindi Sania (2020)
Learning German as a foreign language in Indonesia is possible to apply contextual learning which requires the use of language in daily life. Through the audio visual media, namely instructional videos accompanied by appropriate strategies, the learning process can be helped. In this paper, the Easy German channel is used as one of the online German language learning media with life-based content. This channel presents not only how to talk and think like them properly but their culture and how they live in there. Through the collaboration of online learning media with life-based content, looking forward that it will help the learning process and increase student motivation in German speaking skills.